2015
DOI: 10.1007/s00264-015-2865-9
|View full text |Cite
|
Sign up to set email alerts
|

Oblique femoral shortening osteotomy in total hip arthroplasty for high dislocation in patients with hip dysplasia

Abstract: With the numbers given the oblique femur shortening osteotomy led to an increased rotational stability and proved to be a simple and effective method. Compared with transverse osteotomy and as related to our experience, this technique may be a method of choice in selected cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…2). The reasons we regarded the 8 cm mark below the lesser trochanter the most distant point were the following: (1) most osteotomies located at the proximal femur, including immediately distal to the lesser trochanter [21][22][23][24][25], are at 1-3 cm below the lesser trochanter [7,20,26,27]; and (2) according to Su et al [28], the femoral isthmus begins 8 cm below the lesser trochanter, which influences the stability of the prosthesis and, therefore, osteotomy should not be performed at or beyond this level.…”
Section: Methodsmentioning
confidence: 99%
“…2). The reasons we regarded the 8 cm mark below the lesser trochanter the most distant point were the following: (1) most osteotomies located at the proximal femur, including immediately distal to the lesser trochanter [21][22][23][24][25], are at 1-3 cm below the lesser trochanter [7,20,26,27]; and (2) according to Su et al [28], the femoral isthmus begins 8 cm below the lesser trochanter, which influences the stability of the prosthesis and, therefore, osteotomy should not be performed at or beyond this level.…”
Section: Methodsmentioning
confidence: 99%
“…In restoring the anatomic center of hip rotation in cases of THA for severe DDH, the limb may need to be lengthened greater than 4 cm, placing neurovascular structures at risk of traction injury and increasing the risk of aseptic loosening of components due to excessive joint reactive forces from over-tensioned abductors [19]. In cases where this degree of lengthening is required, subtrochanteric shortening osteotomy of the femur can be performed, which allows for rotational correction of the often over-anteverted femoral neck, in addition to facilitating safe reduction of the hip without compromising neurovascular structures [13,19,20]. If an osteotomy is used, a modular stem, such as the one used in this case, may be beneficial to correct for the often over-anteverted femoral neck seen in DDH, provide good fit in the often hypoplastic femoral canal, obtain torsional stability at the osteotomy site, and allow for easy control of femoral offset and leg lengths [21].…”
Section: Discussionmentioning
confidence: 99%
“…Although some authors have suggested a 45° oblique osteotomy line, to our knowledge, a significant association between line angle and operation outcome has not been established (Fig. ).…”
Section: Direct Anterior Approach Total Hip Arthroplastymentioning
confidence: 91%